Implementing a Web-Based Queue System to Improve Public Service Quality through Participatory Community Engagement - Ahmed J. Obaid; Akbar Iskandar; Riska Kherani; Agung Iqramzah (Jurnal Abdimas Cendekiawan Indonesia, 2026)
Public services in local government procurement units often face issues with queue order and uncertain service times due to reliance on manual processes, which reduces service efficiency and user satisfaction. This condition was observed in the Goods and Services Procurement Work Unit (UKPBJ) of the Pangkep Regency, where service processes remain conventional and lack information system support. This community service activity focused on implementing a web-based queue system integrated with socialization and assistance with system use for the public and service officers. A participatory approach was used, with stages of partner needs analysis, system design and implementation, and impact evaluation, using both qualitative and quantitative methods. Quantitative data were collected from 17 respondents, consisting of six UKPBJ employees and eleven community service users, then analyzed using descriptive statistics. The evaluation results showed an increase in perceptions of queue order, clarity of service information, and certainty of service times, with an average score in the very good category (score > 4.3). In addition, service documentation became more systematic and transparent, supporting data-based decision-making at the institutional level. The contribution of this activity lies in strengthening the technology-based community service model that emphasizes real-world application and social assistance, making it replicable in similar public service units across local government contexts, including developing countries.